Modelo para mensuração de desempenho de uma cadeia de suprimentos da indústria automotiva - Bittencourt, Sandro Augusto Martins (Universidade do Vale do Rio dos Sinos, 2016)
The objective of this thesis was to construct a model of performance measurement applicable to supply chains of the automotive industry. The design of the model was based on the five SCOR processes: planning, supplying, producing, distributing and returning, on the focus of the main competitive dimensions in production strategies: cost, flexibility, delivery, quality and services. The research method was modeling. The proposed model was applied in three consecutive semesters of the supply chain operation composed of a focal company, three suppliers and three distributors. The achievement of focus group discussions with chain managers identified the SCOR processes and the priority competitive dimensions, with the help of the multicriteria Analytic Hierarchy Process (AHP). With the elaboration of the indicator tables, it was possible to capture the performances obtained by the chain links in the three periods analyzed. For the comparisons and totalisation of the results, the indices obtained were relativized in function of the performance objectives attributed to the chain companies. Finally, a temporal comparison with the global performances was developed, where the behaviors and gaps of each SCOR process and of each competitive dimension were discussed. The final results provided the structuring of a conceptual model of performance measurement, which applied in an automotive supply chain pointed the following results: in the second semester of 2014 the performance of the chain was 65.49%, with a gap of 35.41 pp., During this period, the best performances were verified in the process planning and in the competitive dimension quality; the first semester of 2015 chain performance was 68.79%, with a gap of 31.21 pp., wh the best performances were verified in the process planning and at the competitive dimension cost; in the second semester of 2015 chain performance was 73.37% with a gap of 23.63 pp., and the best performances were verified in the planning process planning and the competitive dimension cost.
Keywords: Mensuração de desempenho; Cadeia de suprimentos; SCOR; Analytic hierarchy process; Performance measurement; Supply chain; ACCNPQ::Engenharias::Engenharia de Produção